Love power: From identification to advocacy in fashion sportswear in the social media context - Loureiro, S. M. C.; Rodrigues, Á.; Martins, C. (Journal of Creative Communications, 2024)
There is limited research on how sports fashion brands should develop their strategies to enhance customers’ virtual level of connectedness with companies, taking advantage of the recent expressive growth in social network users. Thus, a new structural model is proposed to analyse the drivers and outcomes of cognitive online brand identification (COBI). This study intends to explore in the sports fashion context (a) the effect of brand prestige and lifestyle congruency on cognitive brand identification, (b) the direct effect of cognitive brand identification on brand advocacy and (c) the indirect effect through brand love. Data were collected using a prolific panel from the United Kingdom and considering individuals that use at least one social media platform to search for and purchase sports fashion clothes (n = 304). The findings indicate that online brand prestige and lifestyle congruency are related to COBI and its outcomes. Although the direct relationship between online brand identification and brand advocacy is not significant, brand love mediates this relationship. Thus, a sports fashion customer is able to forgive any mistake and recommend the sports brand to others, and love towards the brand should be part of the process.